(untitled) (MMIT Proceedings, 2025)
In modern international relations, the growing need for the prompt exchange of information requires states to actively utilize the expanded capabilities of information and communication technologies (ICT) in the implementation of their foreign policy activities. By integrating decision-making mechanisms within governance structures and introducing advanced analytical methods, these processes contribute to the rapid and effective resolution of key issues on the foreign policy agenda. This trend enables countries to strengthen their positions in the international arena, enhancing their adaptability and capacity to respond swiftly to diverse geopolitical situations.